Factors Relating to the Family's Capability in Caring for Patients with Violent Behavior - Sukamti, Nita; Irawan, Toni; Fajariyah, Nur (Sarana Ilmu Indonesia (salnesia), 2025)
One of the significant health problems in Indonesia and the world is mental health. The family is the closest unit for individuals who are facing health problems. The reason of this investigation was to decide whether there's an impact of variables related to the family’s capacity to care for patients with rough behavior at the outpatient clinic of Rs dr. H Marzoeki Mahdi, Bogor. This research used a quantitative method with a cross-sectional design. The research instrument used was the RSES questionnaire to measure knowledge, attitudes, and the family's capability. The testing procedure utilized was purposive inspecting with consideration and avoidance criteria. The sample consisted of 53 subjects. The measurable test utilized was the Chi-Square test. The comes about of this ponder demonstrated that families who were incapable to care for patients with rough behavior summed to 38 subjects (71,7%), which was more than the subjekts who were able to care for patients with violent behavior, which consisted of 15 subjects (28,3%). There's a critical relationship between family demeanors towards patients with savage behavior and the family's failure to care for patients with a p-value of 0,008 and 0,007. The majority of families have good attitudes and knowledge, but it turns out that many of them are lacking in their ability to care for families with problems of violence.